Pembentukan Kelompok Usaha Dan Strategi Branding Untuk Membentuk Identitas Brand Di Daerah Bareng Raya - Desita Nur Rachmaniar; Nisa Isrofi; Riris Ainur Rosidah (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2023)
MSMEs activities in the COVID-19 pandemic situation are of great hope in helping the recovery of the community's economic system. The partners for this community service activity are MSMEs in the Bareng Raya sub-district of Malang. Based on excavations and interviews, it shows that MSMEs in Bareng Raya are still not effective and efficient, especially in the field of branding, because there is still no organization that oversees them. This has an impact on sales results that are less than optimal. Lack of education regarding proper marketing and branding methods is one of the obstacles to marketing outreach to new customers. The approach method used in this community service is the establishment of a business by holding seminars and discussions regarding strategies related to forming business groups and discussion methods regarding possible obstacles. The proposed method is a branding strategy. The science and technology applied to partners includes knowledge of branding strategies to help support the marketing of the Bareng Raya MSMEs business group. In addition, the formation of the Bareng Raya business group will produce output in the form of organizational structure and branding, which are expected to help increase sales.